Factors affecting compliance with the measles vaccination schedule in a Brazilian city - Logullo, Patricia; Carvalho, Heráclito Barbosa de; Saconi, Renata; Massad, Eduardo (São Paulo Medical Journal, 2008)
CONTEXT AND OBJECTIVE: The success of vaccination campaigns depends on the degree of adherence to immunization initiatives and schedules. Risk factors associated with children’s failure to receive the measles vaccine at the correct age were studied in the city of São Paulo, Brazil. DESIGN AND SETTING: Case-control and exploratory study, in the metropolitan area of São Paulo. METHODS: The caregivers of 122 children were interviewed regarding their perceptions and understanding about the measles vaccination and the disease. RESULTS: The results showed that age, region of residence, marital status and education level were unrelated to taking measles vaccines adequately. Most individuals remembered being informed about the last annual vaccination campaign by television, but no communication channel was signifi cantly associated with vaccination status. The answers to questions about knowledge of the disease or the vaccine, when analyzed alone, were not associated with taking measles vaccinations at the time indicated by health agencies. The results showed that, when parents felt sorry for their children who were going to receive shots, they delayed the vaccination. Most of the children did not take the measles vaccination on the exactly recommended date, but delayed or anticipated the shots. CONCLUSION: It is clear that there is no compliance with the government’s recommended measles vaccination schedule (i.e. fi rst dose at nine and second at 15 months of age, as recommended in 1999 and 2000). Feeling sorry for the children receiving shots can delay vaccination taking.